Prognostic Role of Pre-Treatment [18F]FDG PET/CT in Patients with Anaplastic Thyroid Cancer - Hyun Jeong Kim (Cancers, 2021)
Anaplastic thyroid carcinoma (ATC) is a rare but highly lethal disease. Therefore, its diagnosis at an early stage and a rapid and accurate establishment of a proper treatment strategy is warranted. Tumor glycolysis assessed by 18fluorodeoxyglucose ([18F]FDG) positron emission tomography (PET)/computed tomography (CT) is predictive of many cancers despite its limited proven applicability to ATC. We investigated the prognostic capability of [18F]FDG PET/CT in patients with ATC. Forty patients with ATC were subjected to [18F]FDG PET/CT for pre-treatment evaluation. The tumor size and stage, overall survival (OS), and PET parameters, including the maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were analyzed. The 1-year OS rate was 17.5% with a mean life expectancy of 7.1 months. Distant metastasis was detected solely using PET/CT in 37.5% of cases. High SUVmax, MTV, and TLG were significantly associated with poor prognosis (p < 0.001, p = 0.002, and p < 0.001, respectively). A significant difference (p < 0.001) was observed in OS between patients with a high and low tumor SUVmax. Glucose metabolism assessed by [18F]FDG PET/CT was significantly associated with the OS of patients with ATC. PET-derived parameters such as SUVmax, MTV, and TLG are useful prognostic biomarkers for ATC.